PSYCHOLOGICAL FEATURES OF THE FORMATION OF PROFESSIONAL SKILLS IN MEDICAL STUDENTS (TAMADDUN NURI JURNALI, 2025)
this article analyzes the psychological features associated with the development of professional skills in medical students. The article highlights effective psychological strategies for creating a significant learning environment that promotes the acquisition of skills and professional growth through a comprehensive analysis of existing psychological theories and educational practices.